Harmonic Distortion of Blood Pressure Waveform as a Measure of Arterial Stiffness - Milkovich, Nicholas; Gkousioudi, Anastasia; Seta, Francesca; Suki, Béla; Zhang, Yanhang (Frontiers in Bioengineering and Biotechnology, 2022)
Aging and disease alter the composition and elastic properties of the aortic wall resulting in shape changes in blood pressure waveform (BPW). Here, we propose a new index, harmonic distortion (HD), to characterize BPW and its relationship with other in vitro and in vivo measures. Using a Fourier transform of the BPW, HD is calculated as the ratio of energy above the fundamental frequency to that at the fundamental frequency. Male mice fed either a normal diet (ND) or a high fat, high sucrose (HFHS) diet for 2 to 10 months were used to study BPWs in diet-induced metabolic syndrome. BPWs were recorded for 20 seconds hourly for 24 hours, using radiotelemetry. Pulse wave velocity (PWV), an in vivo measure of arterial stiffness, was measured in the abdominal aorta via ultrasound sonography. Common carotid arteries were excised from a subset of mice to determine the tangent modulus using biaxial tension-inflation test. Over a 24-hour period, both HD and systolic blood pressure (SBP) show a large variability, however HD linearly decreases with increasing SBP. HD is also linearly related to tangent modulus and PWV with slopes significantly different between the two diet groups. Overall, our study suggests that HD is sensitive to changes in blood pressure and arterial stiffness and has a potential to be used as a noninvasive measure of arterial stiffness in aging and disease.